2012
DOI: 10.1160/th12-02-0089
|View full text |Cite
|
Sign up to set email alerts
|

Mutation distribution in the von Willebrand factor gene related to the different von Willebrand disease (VWD) types in a cohort of VWD patients

Abstract: Von Willebrand disease (VWD) is the most common inherited bleeding disorder caused by quantitative or qualitative defects of the von Willebrand factor (VWF). VWD is classified into three types--type 1 (partial quantitative deficiencies), type 2 (qualitative defects) and type 3 (complete deficiency of VWF). In this study we explored genotype and phenotype characteristics of patients with VWD with the aim of dissecting the distribution of mutations in different types of VWD. One hundred fourteen patients belongi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 43 publications
(43 reference statements)
6
67
2
Order By: Relevance
“…[19][20][21] We had previously reported a translationally silent mutation c.7464C.T (p.Gly2488) in exon 44 of VWF, 25 bp after the 39ss and 85 bp downstream of the 59ss, in a patient with type 1 VWD. 22 In the present study, in vivo and ex vivo transcript analysis unexpectedly revealed that it inhibited splicing at the 59 donor splice site, despite its 85-bp distance to the 59ss, and led to an aberrant transcript with a retained intronic region in mature mRNA. The previously described mechanisms for exonic substitutions, such as contribution to cisregulatory elements, could not provide a plausible explanation for this event.…”
Section: Introductionmentioning
confidence: 45%
“…[19][20][21] We had previously reported a translationally silent mutation c.7464C.T (p.Gly2488) in exon 44 of VWF, 25 bp after the 39ss and 85 bp downstream of the 59ss, in a patient with type 1 VWD. 22 In the present study, in vivo and ex vivo transcript analysis unexpectedly revealed that it inhibited splicing at the 59 donor splice site, despite its 85-bp distance to the 59ss, and led to an aberrant transcript with a retained intronic region in mature mRNA. The previously described mechanisms for exonic substitutions, such as contribution to cisregulatory elements, could not provide a plausible explanation for this event.…”
Section: Introductionmentioning
confidence: 45%
“…38 However, our reported frequency of VWF sequence variations of 62% in all subjects with type 1 VWD is similar to that reported in several other studies, including the United Kingdom, Canadian, European Union, and German studies. [12][13][14]39 Four subjects with VWF sequence variations had large deletions that would not have been picked up on conventional sequencing but were picked up via comparative genomic hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…16 Interestingly, these gene alterations were associated with either quantitative (types 1 and 3) or qualitative VWD (type 2A). We transiently expressed the mutations in vitro, and characterized their effect on multimer assembly, biogenesis of WPB and secretion.…”
Section: Insights Into Pathological Mechanisms Of Missense Mutations mentioning
confidence: 99%
“…17 Laboratory investigations of VWF antigen (VWF:Ag), VWF ristocetin cofactor activity (VWF:RCo), factor VIII coagulant activity (FVIII:C) and VWF multimers [1.2% (w/v) and 1.6% (w/v) agarose gels] were performed as previously described. 16,18 All mutations were identified by direct sequencing of the VWF coding region as previously described. 16 This study was approved by the local ethics committee and informed consent was obtained from all patients.…”
Section: Patients: Coagulation Studies and Mutation Analysismentioning
confidence: 99%
See 1 more Smart Citation